PERANCANGAN BUKU ILUSTRASI LANDSCAPE BANGUNAN BERSEJARAH DENGAN TEKNIK DIGITAL PAINTING GUNA MENGINFORMASIKAN SEJARAH KEPADA REMAJA DI SURABAYA - Indonesia, Gianluca Lancana; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2017)
Surabaya is known as the City of Heroes because it has a long history during the war of independence 10 November 1945. But many do not know that after the war of independence many historical buildings that witnessed history in liberating the city of Surabaya, for example there are still more than 200 buildings recorded today As a relic and protected by the government of Surabaya and still not many of these buildings are in the know history The purpose of the digital illustration book design of this historic building is to produce a book that contains information about the existence of historical buildings that are not known history and development goals by adolescents and the wider community. The results of this book design of digital illustrations of historic buildings can be one of the media that can inform about the existence of historical buildings that are not known history and development goals by teenagers and the wider community, as well as a medium of introduction of historic buildings to teenagers in the city of Surabaya.Keyword: Illustration Book, History Lesson, Historical Building